Validated measurement of periarticular bone mineral density at the knee joint by dual energy x ray absorptiometry - Murphy, E (2001)
OBJECTIVE—The association of inflammatory arthritis with loss of periarticular bone mineral density (BMD) has been well established. However, changes in bone density cannot be quantified by conventional radiography. This study aimed at developing a new technique for measurement of periarticular bone density at the knee joint by dual energy x ray absorptiometry (DXA) and assessing the precision of this technique for selected areas around the knee. METHODS—To validate this technique for bone density assessment in both patient and control subjects, knee joints from healthy subjects and patients with inflammatory arthritis were selected for study. Posteroanterior (PA) and lateral scans of both knees were acquired with the Hologic 4500 elite bone densitometer. Each scan was repeated three times, with repositioning between scans. Knee scans were obtained with the forearm software and evaluated by subregion analysis. Seven femoral and seven tibial subregions of interest (ROIs) were selected on PA scans. Six ROIs were selected on lateral scans. Precision was determined for each ROI selected. RESULTS—14 knee joints were studied in each group. Precision, expressed as percentage coefficient of variation (CV%), varied widely between subregions. PA scans were most appropriate for measurement of femoral bone density (CV% = 1.89-2.64%), whereas the best value obtained for ROIs within the tibia was on the lateral scan, where CV% for measurement of the proximal 5 mm was 2.67% in the patient group. CV% for BMD of the patella was excellent at 0.84% in the patient group. CONCLUSION—This new application of DXA can be used to measure periarticular bone density at the knee joint. Regions within the distal femur and patella have been identified as the optimal areas to study